Acyclovir Entrapped N-Trimethyl Chitosan Nanoparticles for Oral Bioavailability Enhancement - Medikonduri, Ushasree; Attari, Zenab; Bhat, Krishnamurthy; Lewis, Shaila (Current Nanoscience, 2016)
Objective: The aim of the study was to evaluate a nanoparticulate system composed of Ntrimethyl chitosan (TMC) for improving the oral bioavailability of Acyclovir (ACV). Methods: TMC was prepared by methylation of chitosan and characterized by H-NMR spectroscopy. The ionic gelation method was used to prepare ACV loaded TMC nanoparticles. Non-everted sac technique was used to assess ex vivo permeation in rats. A pharmacokinetic study of the optimized formulation was carried out in male Wistar rats in comparison with ACV alone. Results: Ex vivo studies exhibited a significant rise in the permeation of ACV from the rat intestinal membrane when formulated as nanoparticles. The results showed an increase in plasma concentration of ACV from the nanoformulation and significant difference (p < 0.05) in pharmacokinetic parameters as compared to pure drug, ACV. Conclusion: The results suggest that higher oral delivery of ACV can be achieved by combining the benefits of both TMC and nanoparticles.
Keywords: oral drug delivery